Preschool children’s dental health in the context of mothers role of their children oral hygiene - Gerikienė, Vitalija; Kareivė, Ingrida (Slauga. Mokslas ir praktika, 2020)
The aim of the study: to analyze preschool children’s dental health in the context of mothers role of their children oral hygiene. Materials and methods: The qualitative study was conducted: the case study, applying objective clinical assessment of children’s dental health and structured interview with children’s mothers. The research was attended by 10 preschool age children and their 10 mothers. The purposive sample of research participants was applied. Children’s dental health was identified by checking children’s teeth and calculating DMFT+dft, dmft and OHI-s (DI-s) indexes. Standardized interview contained questions about children mothers’ participation in the process of child oral hygiene and about their knowledge of oral hygiene. Conclusions: In the sample of investigated children oral hygiene is satisfactory (OHI-s (DI-s) index 1.3), caries intensity is low (DMFT+dmft value of 2.5) but close to the limit of moderate caries intensity. Children’s with high caries intensity are poor oral hygiene, their mothers rare participate in the process of child dental health and disinterested in ingredients of child toothpaste and have low awareness of caries preventive measures.